Analisis Efektivitas Pembuatan Produk Cyclone Cone Filter pada Mesin Shearing Ysd di PT. XYZ dengan Metode Overall Equipment Effectivenees (OEE) - Angga Meliansyah Putra; Deri Teguh Santoso; Ratna Anjani (Peneliti.net, 2022)
PT. XYZ which is located in Karawang is engaged in filtering including textile materials, water, oil and gas. Which works closely with several other companies so as to make very high quality products. Therefore, a more efficient, structured and easier work is needed for monitoring. In this study, the preferred goal is to find out how much effective the YSD Shearing Machine is in the manufacture of Cyclone Cone Filter products with the OEE method. The results of the Research on the Effectiveness Level of the YSD Shearing Machine in the Cyclone Cone Filter Production process are 71.98% Week 1, Week 2 87.51%, Week 3 87.33%, Week 4 by 81.32%. And the average calculation result of Overall Equipment Effectiveness is 82.035%. This value does not meet the world standard of 85%.